Enterovirus 71-induced neurological disorders in young gerbils, Meriones unguiculatus: development and application of a neurological disease model. - Ping-Ping Yao; Lei Qian; Yong Xia; Fang Xu; Zhang-Nv Yang; Rong-Hui Xie; Xiao Li; Wei-Feng Liang; Xiao-Xiao Huang; Zhi-Yong Zhu; Han-Ping Zhu (PLoS ONE, 2012)
A reliable disease model mimicking Enterovirus 71 (EV71) infection in humans is essential for understanding pathogenesis and for developing a safe and effective vaccine. Commonly used rodent models including mouse or rat models are not suitable for vaccine evaluation because the rodents are resistant to EV71 infection after they reach the age of 6 days. In this study, 21-day-old gerbils inoculated intraperitoneally (IP) with a non mouse-adapted EV71 strain developed neurological lesion-related signs including hind limb paralysis, slowness, ataxia and lethargy similar to those of central nervous system (CNS) infection of EV71 in humans. The infected gerbils eventually died of the neurological lesions and EV71 could be isolated from lung, liver, spleen, kidney, heart, spinal cord, brain cortex, brainstem and skeletal muscle. Significantly high virus replication was detected in spinal cord, brainstem and skeletal muscle by cellular analysis, real-time quantitative PCR (RT-PCR) and immunohistochemical staining. Histopathologic changes such as neuronal degeneration, neuronal loss and neuronophagia were observed in spinal cord, brain cortex, brainstem, and skeletal muscle along with necrotizing myositis and splenic atrophy. Gerbils that received two doses of inactive whole-virus vaccine showed no EV71-specific symptoms after challenged with EV71. In contrast, gerbils that received mock vaccination died of EV71-induced neuropathology after challenged with EV71. The result indicates that gerbils can serve as a reliable disease model for evaluating safety and efficacy of EV71 vaccine.